Influence of Surwaybest Starch-Based Additive on the Surface Quality of Cast Iron Castings - M. Hrubovčáková; B. Buľko; P. Demeter; S. Hubatka; L. Fogaraš; J. Demeter; D. Dubec; P. Šmigura (Archives of Foundry Engineering)
Though additives developed for foundries are widely used across the globe, their direct effects remain unclear, and the mechanisms of their action within core and moulding mixtures have not yet been precisely described. When utilizing these new additives, it is expected that they will enable the production of castings free from external defects, such as veining or surface flaws. The newly formulated additive, Surwaybest, is composed of iron oxides - specifically magnetite - which promotes cooling through an endothermic reaction while simultaneously generating FeO. The presence of FeO in the core mixture, alongside SiO2, supports the formation of a fayalite layer around the base sand grains, reducing subsurface tension within the mould or core. Surwaybest also contains an insoluble polysaccharide that burns off when the core is cast into the mould, creating space for the quartz base sand to expand. Additionally, it includes carbon, which undergoes dehydrogenation from the molten metal's heat while softening, filling the intergranular spaces, and coating individual grains